Successful surgical treatment for congenital vaginal agenesis accompanied by functional uterus: A report of two cases - Chihiro Minami; Ryosuke Tsunematsu; Kana Hiasa; Katsuko Egashira; Kiyoko Kato (Wolters Kluwer Medknow Publications, 2019)
We present two cases of congenital vaginal agenesis with functional uterine corpus, manifesting with periodic lower abdominal pain and hematometra in adolescence. Both patients were successfully treated with the creation of neovagina and neocanal structures to discharge menstrual blood; this may also facilitate the preservation of fertility. Both cases were characterized by degrees of congenital vaginal agenesis, whether short or completely absent, with no communication between the uterine cavity and external genitalia, as confirmed by physical examination and imaging. We surgically reconstructed a neovagina with the modified McIndoe's procedure, using an artificial skin graft, and canalized to the caudal portion of the uterine cavity. Although redilatation of the neocanal was required, no patient suffered severe infection in postoperative course and both now exhibit regular menstruation. Although hysterectomy has classically been the preferred treatment for such cases, recent technical progression enables treatment of such diseases with conservative and minimally invasive surgery, in a safe manner.